Biobutanol as a promising liquid fuel for the future - recent updates and perspectives. (1st October 2019) - Pugazhendhi, Arivalagan; Mathimani, Thangavel; Varjani, Sunita; Rene, Eldon R.; Kumar, Gopalakrishnan; Kim, Sang-Hyoun; Ponnusamy, Vinoth Kumar; Yoon, Jeong-Jun
Abstract: Butanol is a potential alternative fuel for compensating the depletion of fossil based liquid fuels. Butanol can be easily mixed with either gas or petrol, at any percentage and used as a fuel. Clostridia are the main fermentative organisms used for the production of biobutanol. They are potentially known for their capacity to ferment different types of renewable biomass to butanol through the acetone-butanol-ethanol (ABE) fermentation pathway. This review deals with the mechanism of biobutanol production from biomass feedstocks and the issues and challenges involved in the production of biobutanol. The different types of anaerobic biobutanol production namely fed-batch fermentation, continuous fermentation, and two-stage continuous fermentation have been clearly enunciated. Further, different butanol recovery methods such as adsorption, gas stripping and pervaporation have also been discussed in this review. Certain issues affecting the biobutanol production such as sporulation and solventogenesis have been summarized. These types of problems could be overcome by metabolic engineering of Clostridia, which will enhance the resistance of the microorganisms towards high solvent concentrations and thereby increasing the solvent production. The genetic engineering approach is able to overcome the constraints with wild-type strain by understanding the process of solventogenesis in order to construct or modify the strains with improved downstream processing potential for economically advantageous biobutanol production.